PERAN PEMBINA DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN SANTRI DI PONDOK PESANTREN ALKAUKABUL MUNIR AS’ADIYAH - wasfiyah, faza; Fadil; Nurfadillah; Firanti Mandasari; Faturrahman; Muhammad Asbi; Besse Mutmainnah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the role of tahfidz instructors in improving the quality of Al-Qur'an memorization of students at the Al-Kaukabul Munir As'adiyah Islamic Boarding School, while identifying supporting and inhibiting factors, as well as the instructor's contribution to the tahfidz process. Through a qualitative approach with interview, observation, and documentation methods, this study shows that tahfidz instructors have a strategic role in preparing memorization schedules, tahsin and tahfidz guidance, implementing routine evaluations, and creating a conducive learning environment. Supporting factors for students' success include intrinsic motivation, memory skills, and family support, while obstacles that arise include lack of motivation, concentration disorders, psychological stress, and limited learning environment conditions. The research findings confirm that the instructor's contribution has a significant effect on increasing the quantity and quality of memorization, motivation, independence, and the formation of students' spiritual character, so that improving instructor competence is an important aspect for the success of the tahfidz program as a whole.